1989
DOI: 10.1111/j.1476-5381.1989.tb12625.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of amine metabolizing enzymes on the pharmacology of tyramine in the isolated perfused mesenteric arterial bed of the rat

Abstract: 1 The pressor response to the infusion of tyramine (Tyr) into the isolated perfused mesenteric arterial bed of the rat has been studied at both a low and a high dose (0.2 and 2.0.pmol) and the effect of monoamine oxidase-A (MAO-A) and semicarbazide-sensitive amine oxidase (SSAO) inhibition was examined. Very little MAO-B activity is found in homogenates of this tissue when Tyr is used as substrate.2 Inhibition of SSAO by treating rats with mg kg' (E)-2-(3',4'-dimethoxyphenyl)-3-fluoroally lamine (MDL 72145) 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Elliott et al () investigated amine metabolism in rat isolated mesenteric arteries and found that metabolism of the substrates tyramine and benzylamine was carried out by SSAO and to a lesser extent MAO‐A. Inhibition of both MAO‐A and SSAO (with clorgyline and MDL 72145, respectively) was required to affect contraction of the arteries to tyramine (Elliott et al, ). Studies to assess this effect in arteries with PVAT are needed in addition to studies investigating whether NA is metabolized by SSAO in PVAT.…”
Section: Catecholamine Metabolism By Pvat and Adipose Tissuementioning
confidence: 99%
“…Elliott et al () investigated amine metabolism in rat isolated mesenteric arteries and found that metabolism of the substrates tyramine and benzylamine was carried out by SSAO and to a lesser extent MAO‐A. Inhibition of both MAO‐A and SSAO (with clorgyline and MDL 72145, respectively) was required to affect contraction of the arteries to tyramine (Elliott et al, ). Studies to assess this effect in arteries with PVAT are needed in addition to studies investigating whether NA is metabolized by SSAO in PVAT.…”
Section: Catecholamine Metabolism By Pvat and Adipose Tissuementioning
confidence: 99%
“…SSAO is localized to the outer side of the plasma membrane, allowing it to metabolize circulating amines [28]. Because of the widespread distribution of SSAO in blood vessels other than the aorta [29] and the low plasma SSAO activity, tissue-bound SSAO in vasculature could be hypothesized to be the main site of tresperimus metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of neuronal uptake with cocaine increased the amount of metabolites formed during Tyr infusion. At the concentration used here, cocaine has been shown to potentiate the effects of directly acting sympathomimetic amines and to inhibit the responses to indirectly acting agents, such as Tyr, in this preparation (George & Leach, 1973;Elliott et al, 1989c) indicating that it effectively blocked neuronal uptake. The fact that this resulted in an increase in metabolites leaving the tissue could indicate that the nerve endings in this tissue represented a significant site of accumulation of Tyr from which deaminated metabolites were not readily released.…”
Section: Discussionmentioning
confidence: 99%